Report on the Second International Workshop on Narrative Extraction from Texts (Text2Story 2019) - Jorge, Alípio Mário Guedes (2020)
The Second International Workshop on Narrative Extraction from Texts (Text2Story’19 [http://text2story19.inesctec.pt/]) was held on the 14th of April 2019, in conjunction with the 41st European Conference on Information Retrieval (ECIR 2019) in Cologne, Germany. The workshop provided a platform for researchers in IR, NLP, and design and visualization to come together and share the recent advances in extraction and formal representation of narratives. The workshop consisted of two invited talks, ten research paper presentations, and a poster and demo session. The proceedings of the workshop are available online at http://ceur-ws.org/Vol-2342/